ABOUT NATURE OF YOUNG RUPTURE OF YEGHVARD PLATEAU (Proceedings of the YSU C: Geological and Geographical Sciences, 2004)
The ruptures within Yeghvard plateau that cut upper pliocen - upper quaternary formations were investigated. The description of these ruptures and the nature of their interaction with surrounding rocks are presented. The position of these ruptures within the general structure of Middle-Araksian trough was observed. The conclusion about their voulcano-tectonic nature and comparison with several similar kinds of ruptures of the surrounding area were made.
Keywords: Yeghvard plateau; Middle-Araksian trough; voulcano-tectonic nature; ruptures